ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2010 – 2012 - Andrio Sutriawan; Mulyo Haryanto (Faculty of Economics and Business Diponegoro University, 2014)
The capital market is a means in which treasury securities are long-term traded. Incapital markets, companies get funds relatively expensive, because the company does nothave to pay the capital cost or capital cost can be reduced. Securities that are oftentraded in the capital market is share. Shares are securities as proof of ownership orpossession of individuals and institutions. Many factors affect the stock price like PER,DER, ROA, PBV, NPM and EPS. The purpose of this study was to analyze the effect ofPER, DER, ROA, PBV, NPM and EPS of the stock price.Population and samples in this study are all companies listed on the Stock Exchange ofthe year 2010-2012. Purposive sampling techniques of sampling and obtained a sampleof 333 companies. Type of data is secondary. Methods of data collection using thedocumentation. The analysis technique used is multiple regression.Results of analysis using multiple regression shows that: PER positive effect on the stockprice. DER negative affect the stock price. ROA positive affect the stock price. PBVpositive effect on the stock price. NPM positive effect on the stock price. EPS positiveeffect on the stock price.Keywords : PER, DER, ROA, PBV, NPM, EPS, Stock Price